Ini KEHIDUPAN SOSIAL EKONOMI MASYARAKAT KOTA MOJOKERTO DENGAN ADANYA KEBIJAKAN PEMBANGUNAN TAMAN BAHARI MAJAPAHIT (TBM): Dampak Yang Disadari, Dampak Yang Tidak Disadari - Revi Anggraini; Hikmah Muhaimin; Tri Ratna Rinayuhani (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2024)
This research is motivated by the Presidential Regulation of the Republic of Indonesia Number 80 of 2019 concerning the acceleration of economic development in the Gresik-Bangkalan-Mojokerto-Surabaya-Sidoarjo-Lamongan, Bromo-Tengger-Semeru, and Wilis Circular and Southern Cross regions. To support this regulation, the Mojokerto City Government seeks to develop Tourism Attractions (DTW) which are regulated in the Mojokerto City PERDA Number 7 of 2021 concerning the 2018-2023 Regional Medium-Term Development Plan. This tourism development includes Majapahit Maritime Park (TBM), Mojopahit ship restaurant, PLUT, IKM Center, and road access to tourist sites. The purpose of this study is to analyze the socio-economic impact of the Majapahit Maritime Park (TBM) development policy on the community in Blooto Village, Mojokerto City. This research uses qualitative research methods with data collection techniques through observation, interviews, and documentation. The result is that the impact of the Majapahit Marine Park (TBM) development policy causes physical changes that have an impact on the social and economic aspects of the community. In the social aspect, there is a change in community behavior as well as an increase in the economy seen from buying and selling activities by the local community, which has been predicted due to this tourist attraction.